Mechanistic insights into the renoprotective role of curcumin in cisplatin-induced acute kidney injury: network pharmacology analysis and experimental validation. Issue 2 (20th December 2021) - Hui, Zhang; Dong, Qing-Qing; Shu, Hua-Pan; Tu, Yu-Chi; Liao, Qian-Qian; Yao, Li-Jun
ABSTRACT: Cisplatin-induced acute kidney injury (CP-AKI) is a severe complication in patients receiving CP chemotherapy. However, effective therapies for CP-AKI are currently lacking. Curcumin (CUR), a natural polyphenol, is extracted from the rhizome of turmeric and has been reported to have nephroprotective activity. However, the role of CUR in CP-AKI remains unclear. This study aimed to explore the mechanism of CUR in CP-AKI by combining a network pharmacology approach with experimental validations. The analysis revealed 176 potential targets of CUR based on the HERB database and 1, 286 related targets of CP-AKI from the GeneCards, DrugBank, and OMIM databases. Further, 106 common targets of CUR against CP-AKI were obtained, and these common targets constructed a protein-protein interaction (PPI) network. In addition, the core targets were screened from the PPI network using Cytoscape. Molecular docking revealed that CUR displayed the best binding to AKT1. Gene Ontology (GO) analysis indicated that the primary biological processes of CUR against CP-AKI included cellular response to chemical stress and apoptotic regulation. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis suggested that the PI3K-Akt signaling pathway was most significantly enriched in CUR against CP-AKI. Western blotting and flow cytometry showed that CUR inhibited apoptosis induced by CP by activating the Akt signaling pathway in human kidney tubular epithelial cells (HK-2). Altogether, our findings demonstrated that CUR alleviated apoptosis by activating the Akt signaling pathway in CP-AKI in vitro . These data provide a scientific basis for future investigations into the clinical application of CUR against CP-AKI.